Forage Crop Water Use and Production Under Dryland Conditions - R. Aiken; F. Lamm (Kansas Agricultural Experiment Station Research Reports, 2022)
Forage crops contribute diversity and buffer agronomic risk in water-limited cropping systems. Knowledge of growth responses to uncertain water supply can help guide crop selection and management—including timing of harvest. Our research objective was to determine water use and growth responses of forage winter triticale and forage sorghum under rainfed conditions.
Keywords: water use; forage production; dryland; forage winter triticale; forage sorghum